2021
DOI: 10.1002/anie.202106055
|View full text |Cite
|
Sign up to set email alerts
|

Successive Storage of Cations and Anions by Ligands of π–d‐Conjugated Coordination Polymers Enabling Robust Sodium‐Ion Batteries

Abstract: The oxidation of π–d‐conjugated coordination polymers (CCPs) accompanied with anion insertion has the merits of increasing the capacity and elevating the discharge voltages. However, previous reports on this mechanism either required more investigations or showed low capacity and poor cyclablity. Herein, triphenylene‐catecholate‐based two‐dimensional CCPs are constructed by employing inactive transition‐metal ions (Zn2+) as nodes, forming Zn‐HHTP. Substantial characterizations and theoretical calculations indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 53 publications
8
94
0
Order By: Relevance
“…Subsequently, the 2D honeycomb‐like π‐ d c ‐MOFs HATN‐OCu ( Figure a) and HATN‐SCu (Figure S10, Supporting Information) are prepared by reaction between HATN‐6OH and HATN‐6SR with Cu‐salts respectively at 110 °C for 48 h. Figure 1b displays the powder X‐ray diffraction (PXRD) patterns of HATN‐OCu and HATN‐SCu. Through comparing with the model constructed in the previous reports, [ 26,29 ] it could be found that both c ‐MOFs tend to exhibit an AA′ stacking mode. Considering the different bond lengths of CuS and CuO, we establish two model structures to further study the structures of HATN‐OCu and HATN‐SCu (Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Subsequently, the 2D honeycomb‐like π‐ d c ‐MOFs HATN‐OCu ( Figure a) and HATN‐SCu (Figure S10, Supporting Information) are prepared by reaction between HATN‐6OH and HATN‐6SR with Cu‐salts respectively at 110 °C for 48 h. Figure 1b displays the powder X‐ray diffraction (PXRD) patterns of HATN‐OCu and HATN‐SCu. Through comparing with the model constructed in the previous reports, [ 26,29 ] it could be found that both c ‐MOFs tend to exhibit an AA′ stacking mode. Considering the different bond lengths of CuS and CuO, we establish two model structures to further study the structures of HATN‐OCu and HATN‐SCu (Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 74%
“…Based on these intrinsic advantages, Wang et al constructed the triphenylene catecholate‐based 2D π‐d conjugated coordination polymers (Zn‐HHTP) with Zn 2+ as the anodes. [ 26 ] It revealed that the stable electrochemical properties (high capacity retention of 90% at 0.1 A g −1 after 1000 cycles) in SIBs were derived from its distinctive storage mechanism: only the [ZnO 4 ] unit of the ligand as single active center continuously store cations and anions via three‐electron reactions. Additionally, Xia et al.…”
Section: Introductionmentioning
confidence: 99%
“…S25 (ESI‡), the peaks at 2 θ = 12.16 (001) and 18.13° (110) showed a slight shift to lower angles when being discharged to 1.0 V, indicating that the insertion of Na + ions into Ni-DHBQ resulted in the increase of the lattice constant. However, further embedding of Na + ions increased the interactions between the skeletons by the Na + ions, causing the shrinking of the unit cell, after being discharged to 0.01 V, 20 although the intensity became weak. When the Ni-DHBQ electrode was fully charged, the lattice parameters returned to the initial states, indicating the reversibility of Ni-DHBQ .…”
Section: Resultsmentioning
confidence: 99%
“…16–19 There is no doubt that the electrochemical behaviours of CCPs could be enhanced by the judicious choice of organic ligands and metals to ensure high-performance metal-ion batteries. 20–26 However, due to the complicated synthesis process, including in situ deprotonation, oxidation, and coordination, the rational design and controllable synthesis of CCPs remain challenging, which prevents the deep understanding of charge storage mechanisms and gaining insight into the relationship between the structure and the electrochemical performance and limits the potential applications of CCPs. 27–31…”
Section: Introductionmentioning
confidence: 99%
“…The core‐level O1 s spectrum in Figure 4c and Figure S17b, Supporting Information, can be deconvoluted into two different components at the binding energies of 531.4 and 533.0 eV, corresponding to the configuration of CO and C=O, respectively. [ 30,31 ] The decreasing intensity of the C = O double bond and the increasing intensity of the CO single bond peak can be seen as the proceeding of the charging operation, indicating the transformation reaction from C=O double bond to CO single bond due to the insertion of Na + ions. [ 16 ] O1 s core‐level with a new peak position of 536.0 and 535.6 eV can also be observed in Co‐CAT/Na 2 SO 3 and Ni‐CAT/ Na 2 SO 3 after the voltage of −0.3 V, respectively, corresponding to the O atom of SO 3 2− .…”
Section: Resultsmentioning
confidence: 99%